Effects of pregnancy status on organic anion transporters and prostaglandin receptors in equine endometrium during maternal recognition of pregnancy - Cleys, Ellane R., author; Bruemmer, Jason, advisor; Hansen, Thomas, committee member; Denniston, David, committee member; Bouma, Gerrit, committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Keywords: Mares -- Reproduction; Endometrium; Prostaglandins